2017
DOI: 10.3168/jds.2016-12300
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of antibody response to paratuberculosis in dairy cattle

Abstract: Genetic parameters were estimated for antibody response to paratuberculosis (Mycobacterium avium ssp. paratuberculosis) using milk ELISA test results, collected and analyzed by National Milk Records, from Holstein Friesian cows on UK dairy farms in their first 3 lactations. Milk ELISA test results were obtained from 2007 to 2012 and combined with milk recording data and pedigree information. The reduced data set edited for the purposes of genetic parameter estimation consisted of 148,054 milk ELISA records fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Differences among these studies may be due to many factors such as various diagnostic tests, variable disease incidence in the studied populations, different management practices, the population under investigation (as genetic parameters are population-specific), trait definitions, statistical models, pedigree depth, data editing, and others. In our study, maternal effects were not a significant source of variation (P > 0.05) and, therefore, were not included in the statistical models; this is in agreement with other studies that reported contribution of maternal effects to JD phenotypic variance lower than 1.5% (Mortensen et al, 2004;Attalla et al, 2010;Pritchard et al, 2017a).…”
Section: Estimation Of Genetic Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Differences among these studies may be due to many factors such as various diagnostic tests, variable disease incidence in the studied populations, different management practices, the population under investigation (as genetic parameters are population-specific), trait definitions, statistical models, pedigree depth, data editing, and others. In our study, maternal effects were not a significant source of variation (P > 0.05) and, therefore, were not included in the statistical models; this is in agreement with other studies that reported contribution of maternal effects to JD phenotypic variance lower than 1.5% (Mortensen et al, 2004;Attalla et al, 2010;Pritchard et al, 2017a).…”
Section: Estimation Of Genetic Parameterssupporting
confidence: 91%
“…A higher genetic merit for milk yield was not associated with higher susceptibility to MAP infection. In general, Pritchard et al (2017a) reported significant positive genetic correlations between milk antibody response and udder health traits such as log-transformed SCC and number of mastitis episodes, implying that animals predisposed to higher SCC or mastitis may also mount a higher antibody response during MAP infection; therefore, selection for lower MAP antibody response could be favorable for udder health. Shook et al (2012) reported unfavorable genetic correlations that ranged from 0.14 to 0.22 for MAP infection with milk production traits; however, these estimates were associated with high confidence intervals that also contained zero values.…”
Section: Correlations With Other Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Lynch and Walsh, 1998). Heritability estimates for LM and TPM are in good agreement with previous reports of linear model heritability estimates, which ranged from <0.01 to 0.183 (Koets et al, 2000;Mortensen et al, 2004;Gonda et al, 2006;Hinger et al, 2008;Attalla et al, 2010;Berry et al, 2010;van Hulzen et al, 2011;Zare et al, 2014;Pritchard et al, 2017), and previous threshold model estimates, which ranged from 0.052 to 0.283 (Gonda et al, 2006;Hinger et al, 2008;Attalla et al, 2010;Berry et al, 2010;Küpper et al, 2012;Shook et al, 2012;Zare et al, 2014). Heritability estimates increased as data were restricted to herds with presumed higher MAP exposure for both linear and threshold model analyses, as previously observed (van Hulzen et al, 2011).…”
Section: Short Communication: Heritability Of Susceptibility To Infecsupporting
confidence: 89%
“…studies, heritability for serum total protein (STP) and some immunoglobulins (Ig) were estimated in some studies (Jensen and Christensen 1975;Jensen et al 1982;Mallard et al 1983;Muggli et al 1984;Mazengara et al 1985;Gilbert et al 1988a;Burton et al 1989;Detilleux et al 1994). On the other hand, while in some studies genetic parameters for natural antibodies associated with mastitis ( Thompson-Crispi et al 2013) and antibody development against paratuberculosis (Pritchard et al 2017) were estimated in the Holsteins, some other studies focused on the development of resistance to the bovine respiratory disease through selection (Snowder et al 2006;Snowder 2009;Cockrum et al 2016).…”
mentioning
confidence: 99%